2021
DOI: 10.1155/2021/5545261
|View full text |Cite
|
Sign up to set email alerts
|

Ndufs1 Deficiency Aggravates the Mitochondrial Membrane Potential Dysfunction in Pressure Overload‐Induced Myocardial Hypertrophy

Abstract: Mitochondrial dysfunction has been suggested to be the key factor in the development and progression of cardiac hypertrophy. The onset of mitochondrial dysfunction and the mechanisms underlying the development of cardiac hypertrophy (CH) are incompletely understood. The present study is based on the use of multiple bioinformatics analyses for the organization and analysis of scRNA-seq and microarray datasets from a transverse aortic constriction (TAC) model to examine the potential role of mitochondrial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…Of those genes, three were closely associated with mitochondrial energy metabolism (NDUFS1, HADHB, and ALDOA) and were significantly upregulated in the LRFI group. NDUFS1 encodes one subunit of mitochondrial complex I, which is mainly involved in transferring electrons and maintaining the redox balance (Zou et al, 2021) in the first step of oxidative phosphorylation (Bertile et al, 2021). Knockdown of the NDUFS1 gene reduces membrane potential and mitochondrial mass in cardiomyocytes while also causing increased ROS production (Ni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those genes, three were closely associated with mitochondrial energy metabolism (NDUFS1, HADHB, and ALDOA) and were significantly upregulated in the LRFI group. NDUFS1 encodes one subunit of mitochondrial complex I, which is mainly involved in transferring electrons and maintaining the redox balance (Zou et al, 2021) in the first step of oxidative phosphorylation (Bertile et al, 2021). Knockdown of the NDUFS1 gene reduces membrane potential and mitochondrial mass in cardiomyocytes while also causing increased ROS production (Ni et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…NADH is produced mainly through the electron respiratory chain to generate large amounts of ATP for life activities. The three identified DEGs-HADHB, ALDOA, and NDUFS1-are essential for fatty acid β-oxidation (Kao et al, 2006), glycolysis (Fu et al, 2018), and the function of the electron transport chain complex I, respectively (Zou et al, 2021). Moreover, other DEGs, such as CUL1 signigicantly down-regulated in the LRFI group (knockdown can lead to oxidative injury) (Goo et al, 2017), RFN4 signigicantly up-regulated in the LRFI group (deficiency of it can result in mitochondrial stress) (Syota et al, 2008), LDAH signigicantly down-regulated in the LRFI group (it plays a primarily lipogenic role (MoranKatz et al, 1998)), INPPL1 signigicantly down-regulated in LRFI group (it shows a capacity to impair insulin signaling (Ueno and Nakazato, 2016)), were also involved in substance or energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are double-membrane organelles that support a variety of physiological activities, including energy production, cell death and oxidative metabolism (9). Mitochondrial dysfunction has been implicated in the occurrence and development of cardiomyocyte hypertrophy (28). Mitochondrial biogenesis is essential for sustaining mitochondrial function and is related to ROS production (29).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that Ndusf1 was downregulated in TAC mouse models. Further gain- and loss-of-function analysis revealed that Ndusf1 deficiency deteriorated cardiac hypertrophic response ( 44 ). In vitro mechanistic exploration showed that the mitochondrial DNA content in CMs was significantly decreased after Ndusf1 deletion, consistently, loss of Ndusf1 dramatically elevated ROS production in CMs.…”
Section: Mechanisms Linking Mitochondria and Pathological Cardiac Hypertrophymentioning
confidence: 99%